Antidiarrheal activity of methanolic leaf and bark extracts of cinnamomum mercadoi vidal. - Gorgonio, Stan Rey P. (Tacloban City Stan Rey P. Gorgonio, 2010)
The antidiarrheal activity of the leaves and bark of C. mercadoi Vidal (CMV-M) was evaluated on experimental diarrhea models in mice. The methanolic leaf and bark extract of C. mercadoi Vidal (250 and 500 mg/kg body weight) were administered by orogastric gavage to four groups of mice (five animals per group) in order to evaluate the activity of the extract against castor oil-induced diarrhea in mice. Two control groups were prepared: one received distilled water (10ml/kg) as negative controland the other loperamide (3mg/kg) as positive control. The effect of the extract on normal intestinal transit was assessed by gastrointestinal (GI) motility test via charcoal meal marker. In the mice with castor oil-induced diarrhea, at oral dose of 250 and 500 mg/kg body weight, the bark extract showed pronounced and dose-dependent antiddiarrheal activity. The protective role of the bark extract at 500 mg/kg was more than that of the reference drug, loperamide (3mg/kg). The bark extract (500mg/kg) produced a decrease in intestinal transit comparable to loperamide (3mg/kg) at p<0.05 level of significance. Although the leaf extracts inhibited an inhibitory effect on castor oil-induced diarrhea and GI motility test, the results were not significantly different from the negative control group. The inhibitory effect of the bark extract (CMV-M) on castrol oil induced diarrhea model and gastrointestinal motility induced diarrhea model and gastrointestinal motility test provides pharmacological evidence of its antidiarrheal activity.
Undergraduate thesis (B.S. Biology)--University of the Philippines, Tacloban